(untitled) (Oxford, 1997)
Let's Go is a series for those who are just beginning their study of English. It combines a carefully controlled, grammar-based syllabus with practical language. Functional dialogues, interactive games, and pair-work activities foster a lively and motivating classroom environment
Keywords: English language; Study and teaching,Textboooks foreign speakers